Differential co-expression analysis of human cancers to reveal systems biomarkers for diagnostic and therapeutic trials - Erdöl, Meltem Nur (My University, 2019)
İNSANLARDA GÖRÜLEN KANSER TÜRLERİ İÇİN TEŞHİS VE TEDAVİ AMAÇLI SİSTEM BİYOBELİRTEÇLERİNİN DİFERANSİYEL KO-EKSPRESYON YÖNTEMİ İLE BELİRLENMESİSistem biyolojisinde yeni bir yaklaşım olan diferansiyel ortak ifade analizi, geleneksel diferansiyel gen ekspresyon analizine tamamlayıcı bir yöntem olarak ortaya çıkmıştır. Hastalıkların genetik altyapısını anlamak için, hastalıklı ve sağlıklı koşullarda genlerin etkileşimlerini ortaya koymak önemlidir. Bu çalışmada, bazı kanser türleri (mide kanseri, küçük hücreli dışı akciğer kanseri, pankreas kanseri) diferansiyel ortak ifade analizi altonda incelenmiş ve bu sonuçların kanserdeki tanı ve tedavi uygulamalarının araştırılmasında nasıl kullanılabileceği tartışılmıştır. İlgili gen ekspresyon verileri, Ulusal Biyoteknoloji Bilgi Merkezi (NCBI) veri tabanından elde edilmiştir. Diferansiyel olarak ifade edilen genleri karakterize etmek için, her bir veri seti normalize edilmiş ve istatistiksel analizler gerçekleştirilmiştir. Ko-ekspresyon profilleri, incelenen her bir kanser türünün ekspresyonlarında farklılık gösteren gen kümelerinden oluşturulmuş ve genetik ağlar, hasta ve sağlıklı bireylerde farklı şekilde ifade edilip edilmediğini belirtmek için kurulmuştur. Bu ağların son derece etkileşimli alt kümeleri modül olarak atanmış ve bu modüllerin, kanserlerin tanı ve tedavi uygulamaları için önemli olup olmadığı araştırılmıştır.

DIFFERENTIAL CO-EXPRESSION ANALYSIS OF HUMAN CANCERS TO REVEAL SYSTEMS BIOMARKERS FOR DIAGNOSTIC AND THERAPEUTIC TRIALSDifferential co-expression analysis, a new approach in systems biology, has emerged as a complementary method to traditional differential gene expression analysis. In order to understand the genetic background of diseases, it is important to reveal the interactions of genes in diseased and healthy conditions. In this study, several cancer types (gastric carcinoma, non-small cell lung carcinoma, pancreatic ductal adenocarcinoma) were examined using differential co-expression analyses and it was discussed how these results could be used for research of diagnostic and therapeutic applications in cancer. The relevant gene expression data were obtained from National Centre for Biotechnology Information (NCBI) database. In order to characterize the differentially co-expressed genes, the normalization of each data set and statistical analyses were performed. Co-expression profiles were constructed from gene clusters that differ in their expression in each type of cancer examined and genetic networks were established to indicate whether they were expressed differently in tumour and healthy individuals. Highly interacting sub-clusters of these networks were assigned as modules and these modules were investigated whether they are significant for diagnostic and therapeutic applications of cancer.
Keywords: Bioengineering; biyoinformatik; Biyomühendislik; cancer; co-expression analysis; kanser bioinformatics; ko-ekspresyon analizi; Tumors; Tümörler